2018
DOI: 10.1007/s11356-018-1345-3
|View full text |Cite
|
Sign up to set email alerts
|

Fullerene C60 for enhancing phytoremediation of urea plant wastewater by timber plants

Abstract: Phytoremediation has been applied as a promising and cost-effective technique for removing nutrient pollutants from wastewater. In this study, the effect of fullerene C60 was assessed on enhancing the phytoremediation efficiency of teak plants over a period of 1 month. Teak plants were supplied with fullerene C60 (0, 25, or 50 mg L) and fed daily with two types of urea plant wastewater (with and without adding optimum ratio of phosphorus and potassium). The required volume of wastewater by the teak plants, nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…On the other hand, others reported that biochar has the capacity to remove or enhance phosphorus removal [4,5,7,13]. The apparently conflicting findings can be explained by the fact that the characteristics of biochar depend on the parent biomass and preparation conditions which affect their adsorption capacity of different chemicals [9,14].…”
Section: Ammonium Removalmentioning
confidence: 99%
“…On the other hand, others reported that biochar has the capacity to remove or enhance phosphorus removal [4,5,7,13]. The apparently conflicting findings can be explained by the fact that the characteristics of biochar depend on the parent biomass and preparation conditions which affect their adsorption capacity of different chemicals [9,14].…”
Section: Ammonium Removalmentioning
confidence: 99%